Biochemical Indicators of Fruits of Melon Varieties Suitable for Storage in the Conditions of the Republic of Karakalpakstan - Sultanov Jetkerbay Davletbayevich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article presents information on the biochemical parameters of the fruits of melon varieties grown in the climate conditions of the Republic of Karakalpakstan.